2(m+2)=11

Simple and best practice solution for 2(m+2)=11 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2(m+2)=11 equation:


Simplifying
2(m + 2) = 11

Reorder the terms:
2(2 + m) = 11
(2 * 2 + m * 2) = 11
(4 + 2m) = 11

Solving
4 + 2m = 11

Solving for variable 'm'.

Move all terms containing m to the left, all other terms to the right.

Add '-4' to each side of the equation.
4 + -4 + 2m = 11 + -4

Combine like terms: 4 + -4 = 0
0 + 2m = 11 + -4
2m = 11 + -4

Combine like terms: 11 + -4 = 7
2m = 7

Divide each side by '2'.
m = 3.5

Simplifying
m = 3.5

See similar equations:

| 4w^2+20w=0 | | 10(7)+100x=30(7+x) | | 4H+15=8-3H | | 10x-7=6x-21 | | 11n-3=9n+5 | | 10x-7=6x-12 | | -(9x-3)-(5x-5)+7=-9(x-1)-(9x+9)+3 | | 12+5L=30-4L | | 6x-13-4x=4x-8 | | 100=Y+(Y*.02) | | 5V+3-2V=4V | | 2p-5=27 | | 5y+2(y-6)=7y-2(y-10) | | -4.5b=1.8 | | 6x=21.6 | | 5x-2(x-9)=3(x+1)+3 | | ln(x)=ln(12)-2ln(3) | | 100=Y+(Y*.05) | | x+3=12x-8 | | .24n=95 | | 7=6+2y | | 6+2y= | | x*(18/8-300)-4=-4 | | 3(1+1X)=15 | | 4sin(2*pi*x)=2 | | (4x+9)-(-3x*-3x-5x+9)= | | =p^3-5p^2q-24pq^2 | | 16=-16x^2+32x | | 3(3-1)+(-3*-3)-4= | | 6(6-3)+(-6)-6-4= | | p^3+p^2q-56pq^2= | | 24(-2x+1)=-7(5x+2)-3x |

Equations solver categories